Efficacy of psychosensory interventions for the management of pediatric pain, fear, and distress during emergency care: a systematic review and meta-analysis of randomized clinical trials - Bustamante Fernández, Mariela; Caes, Line; Rossel, José Iván; Díaz Díaz, Genesis; Ruiz Valenzuela, Gabriela; Caroca Madariaga, Scarlett; Klein Vallecillo, Nicole; Hidalgo Vilche, Sofía; Tapia Espinoza, Valeska; González Zamarin, Mariana; Strasser, Katherine (Frontiers in Pediatrics, 2026)
The experience of invasive medical procedures (IMP) in pediatric emergency departments (PEDs) is often highly stressful for children and adolescents and potentially leads to short- and long-term biopsychosocial consequences. To address these challenges, psychological and sensory strategies have been developed to mitigate negative outcomes and enhance children's adaptive coping PEDs. ObjectiveTo evaluate the efficacy of psychological and sensory interventions on pediatric pain, fear, and distress during PEDs.MethodsA systematic review and meta-analysis were conducted following the PRISMA 2020 Statement (PROSPERO registration: CRD42023403583). Searches were performed in PubMed, PsycInfo, CINAHL, SCOPUS, and Web of Science for studies published between January 2004 and September 2024. Randomized controlled trials involving children aged 2–18 years undergoing IMPs in PEDs. The qualitative synthesis and meta-analysis were performed using the Review Manager (RevMan) web versioN.Effect sizes were estimated using Z-scores (Z), p-values (p), and standardized mean differences (SMD).ResultsA total of 1,796 records were retrieved (PubMed = 513, PsycInfo = 148, CINAHL = 516, SCOPUS = 183, Web of Science = 436); 45 were retained for the meta-analysis. Psychosensory interventions were grouped into seven subcategories: Somato-Sensory, Immersive Reality, Screen-Based, Toy Interaction, Social Interaction, Active Command, and Unisensory Distractions. The meta-analysis revealed significant reductions in both self-reported pain and fear (Z = 7.66/6.18, p < 0.01; SMD = −0.94/−1.30) and observed pain and fear (Z = 6.27/5.28, p < 0.01; SMD = −1.52/−1.77) across all intervention categories. The most effective interventions were pre-procedural informational videos (Z = 21.54/21.24, p < 0.01; SMD = −2.40/−2.18) and somato-sensory procedural distraction (Z = 5.37, p < 0.01; SMD = −1.08). Playful social interaction strategies (Z = 7.38, p < 0.01; SMD = −1.20), behavioral command (Z = 6.22/4.41, p < 0.01; SMD = −1.05/−0.87), and immersive reality (Z = 4.66, p < 0.01; SMD = −0.95) were also found to reduce observer-reported distress. However, a high degree of heterogeneity was observed in the results (I2 > 90%/98), which warrants a cautious interpretation.DiscussionBoth pre-procedural preparation strategies and somatosensory procedural distractions are promising approaches for managing stressful experiences in PED settings. These approaches may address the sensory, cognitive, and emotional components of procedural pain, fear and distress. The evidence obtained could inform the development of clinical protocols aimed at optimizing children' experiences in PEDs and potentially minimizing long-term psychological and somatosensory consequences.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?ID=CRD42023403583, PROSPERO CRD42023403583.